Early Heparin Administration Attenuates Tissue Factor‐Mediated Thrombin Generation During Simulated Cardiopulmonary Bypass. Issue 1 (25th November 2013) - Morizumi, Sei; Hiramatsu, Yuji; Matsuzaki, Kanji; Goto, Yukinobu; Sato, Shoko; Abe, Masakazu; Kato, Hideyuki; Matsubara, Muneaki; Sakakibara, Yuzuru
Abstract Background We tested the hypothesis that heparin administration prior to the emergence of tissue factor (TF) would increase plasma TF pathway inhibitor (TFPI) and attenuate TF‐mediated thrombin generation during simulated cardiopulmonary bypass (CPB). Methods Human blood was recirculated for 120 minutes using an oxygenator and roller pump. Four groups were examined: control group (heparin 3.75 U/mL, in donor blood, n = 7), rTF group (heparin + recombinant TF 1000 pg/mL, in donor blood, n = 7), TFPI boost group (heparin, in preheparinized donor blood, n = 8), and rTF + TFPI boost group (heparin + rTF, in preheparinized blood, n = 7). In the two TFPI boost groups, 50 U/kg of heparin was given to the donors intravenously five minutes before donation to boost plasma TFPI levels. Total plasma TFPI, thrombin–antithrombin complex, and prothrombin fragment F1+2 levels were measured before and during CPB. Results Preheparinization increased total plasma TFPI levels by a factor of 8.0. Administration of rTF significantly enhanced the generation of F1+2 (p = 0.0002). The heparin‐induced TFPI elevation reduced both thrombin–antithrombin complex and F1+2 to control levels in rTF + TFPI boost group (p = 0.0158 for thrombin–antithrombin complex, p < 0.0001 for F1+2). F1+2 levels were at all times lower than control levels in TFPI boost group (p < 0.0001). Conclusions Heparin‐induced TFPI elevation attenuates TF‐mediated thrombin generation. Early heparin administration prior to the emergence of plasma TF may represent a novel strategy for controlling thrombin generation by the extrinsic coagulation pathway during CPB. doi: 10.1111/jocs.12254 (J Card Surg 2014;29:35‐40)